Use f ( x ) = x 2 − x , f(x)=x 2 −x, g ( x ) = 9 − 2 x g(x)=9−2x, and h ( x ) = x 2 + 2 x − 63 h(x)=x 2 +2x−63. Find ( f + h ) ( x ) (f+h)(x).

Respuesta :

Given:

The functions are:

[tex]f(x)=x^2-x[/tex]

[tex]g(x)=9-2x[/tex]

[tex]h(x)=x^2+2x-63[/tex]

To find:

The function [tex](f+h)(x)[/tex].

Solution:

We know that,

[tex](f+h)(x)=f(x)+h(x)[/tex]

Substituting the values of given functions, we get

[tex](f+h)(x)=x^2-x+x^2+2x-63[/tex]

[tex](f+h)(x)=2x^2+x-63[/tex]

Therefore, the required function is [tex](f+h)(x)=2x^2+x-63[/tex].

ACCESS MORE